THE INFLUENCE OF WORK ENVIRONMENT AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE IN THE SOCIAL SERVICES DEPARTMENT OF TANGERANG CITY - Virlo, Versen; Herayati, Herayati; Windasari, Vicky (Jurnal Manajemen Perbankan Keuangan Nitro, 2025)
This study analyzes the effect of Work Environment and Organizational Culture on Employee Performance at the Social Service Office of Tangerang City. Using a quantitative approach, questionnaires were distributed to 49 respondents and data were processed with SPSS 23 through validity, reliability, classical assumption, and hypothesis testing (t-test, F-test, and R²). Results show that the Work Environment significantly and positively affects employee performance (sig. 0.036 < 0.05; t-count 2.160 > t-table 1.679), while Organizational Culture has a highly significant positive effect (sig. 0.000 < 0.05; t-count 10.037 > t-table 1.679). Simultaneously, both variables significantly influence performance (sig. 0.000 < 0.05; F-count 67.781 > F-table 3.230). The coefficient of determination reveals that 77.1% of performance variation is explained by these two factors, with the remainder influenced by others. The study concludes that Work Environment and Organizational Culture are key drivers of employee performance.